Gene editing in tree and clonal crops: progress and challenges - Goralogia, Greg S.; Redick, Thomas P.; Strauss, Steven H. (In vitro cellular & developmental biology. Plant, 2021)
Because of the limitations inherent in conventional breeding of trees and clonally propagated crops, gene editing is of great interest. Dozens of published papers attest to the high efficiency of CRISPR-based systems in clonal crops and trees. The opportunity for "clean" edits is expected to avoid or reduce regulatory burdens in many countries and may improve market acceptance. To date, however, nearly all studies in trees and clonal crops retained all of the gene editing machinery in the genome. Despite high gene editing efficiency, technical and regulatory obstacles are likely to greatly limit progress toward commercial use. Technical obstacles include difficult and slow transformation and regeneration, delayed onset of flowering or clonal systems that make sexual segregation of CRISPR-associated genes difficult, inefficient excision systems to enable removal of functional (protein- or RNA-encoding) transgenic DNA, and narrow host range or limited gene-payload viral systems for efficient transient editing. Regulatory obstacles include those such as in the EU where gene-edited plants are regulated like GMO crops, and the many forms of method-based systems that regulate stringently based on the method vs. product novelty and thus are largely applied to each insertion event. Other major obstacles include the provisions of the Cartagena Protocol with respect to international trade and the need for compliance with the National Environmental Policy Act in the USA. The USDA SECURE act has taken a major step toward a more science- and risk-based—vs. method and insertion event based—system, but much further regulatory and legal innovation is needed in the USA and beyond.